How students taking introductory biology experience the chemistry content - Lilyan Mendez; Angelita T. Rivera; Izabella Vasquez; Alfonso Godínez Aguilar; Melinda T. Owens; Clara L. Meaders (Journal of Microbiology & Biology Education)
ABSTRACT Student experiences learning chemistry have been well studied in chemistry courses but less so in biology courses. Chemistry concepts are foundational to introductory biology courses, and student experiences learning chemistry concepts may impact their overall course experiences and subsequent student outcomes. In this study, we asked undergraduate students enrolled in introductory biology courses at a public R1 institution an open-response question asking how their experiences learning chemistry topics affected their identities as biologists. We used thematic analysis to identify common ideas in their responses. We found that while almost half of student respondents cited learning chemistry as having positive impacts on their experiences learning biology, students who struggled with chemistry topics were significantly more likely to have negative experiences learning biology. We also found significant relationships between prior chemistry preparation, student background, and the likelihood of students struggling with chemistry and negative experiences learning biology. These findings emphasize the impact of learning specific content on student psychosocial metrics and suggest areas for biology educators to focus on to support learning and alleviate student stress in introductory biology.